Sedum spiralifolium (Crassulaceae): a new species from Anhui Province, China - Xie, Dong Mei; Peng, Dai-Yin; Fang, Cheng-Wu; Qin, Min-Jian; Wang, De-Qun; Huang, Lu-Qi (Phytotaxa, 2014)
A new species of Sedum, S. spiralifolium from Anhui Province, eastern China is described and illustrated. Our molecular systematics results (based on nuclear ITS and plastid trnL-trnF) and morphological analyses indicate that this new species is closest to S. sarmentosum. It differs from S. sarmentosum by having linear-lanceolate leaves, earlier flowering and twisted upper leaves at the top of its sterile shoots.